A Large Cohort of Hemoglobin Variants in Thailand: Molecular Epidemiological Study and Diagnostic Consideration - Srivorakun, Hataichanok; Singha, Kritsada; Fucharoen, Goonnapa; Sanchaisuriya, Kanokwan; Fucharoen, Supan (PLOS ONE, 2014)
Background Hemoglobin (Hb) variants are structurally inherited changes of globin chains. Accurate diagnoses of these variants are important for planning of appropriate management and genetic counseling. Since no epidemiological study has been conducted before, we have investigated frequencies, molecular and hematological features of Hb variants found in a large cohort of Thai subjects. Materials and Methods Study was conducted on 26,013 unrelated subjects, inhabiting in all geographical parts of Thailand over a period of 11 years from January 2002-December 2012. Hb analysis was done on high performance liquid chromatography (HPLC) or capillary electrophoresis (CE). Mutations causing Hb variants were identified using PCR and related techniques. Results Among 26,013 subjects investigated, 636 (2.4%) were found to carry Hb variants. Of these 636 subjects, 142 (22.4%) carried α-chain variants with 13 different mutations. The remaining included 451 (70.9%) cases with 16 β-chain variants, 37 (5.8%) cases with Hb Lepore (δβ-hybrid Hb) and 6 (0.9%) cases with a single δ-chain variant. The most common α-globin chain variant was the Hb Q-Thailand (α74GAC-CAC, Asp-His) which was found in 101 cases (15.8%). For β-globin chain variants, Hb Hope (β136GGT-GAT, Gly-Asp) and Hb Tak (β146+AC, Ter-Thr) are the two most common ones, found in 121 (19.0%) and 90 (14.2%) cases, respectively. Seven Hb variants have never been found in Thai population. Hb analysis profiles on HPLC or CE of these variants were illustrated to guide presumptive diagnostics. Conclusions Hb variants are common and heterogeneous in Thai population. With varieties of thalassemias and hemoglobinopathies in the population, interactions between them leading to complex syndromes are common and render their diagnoses difficult in routine practices. Knowledge of the spectrum, molecular basis, genotype-phenotype correlation and diagnostic features should prove useful for prevention and control of the diseases in the region.